Stimuli‐Responsive Cycloaurated "OFF‐ON" Switchable Anion Transporters. Issue 40 (11th August 2020) - Fares, Mohamed; Wu, Xin; Ramesh, Deepthi; Lewis, William; Keller, Paul A.; Howe, Ethan N. W.; Pérez‐Tomás, Ricardo; Gale, Philip A.
Abstract: Anion transporters have shown potential application as anti‐cancer agents that function by disrupting homeostasis and triggering cell death. In this research article we report switchable anion transport by gold complexes of anion transporters that are "switched on" in situ in the presence of the reducing agent GSH by decomplexation of gold. GSH is found in higher concentrations in tumors than in healthy tissue and hence this approach offers a strategy to target these systems to tumors. Abstract : Bis‐imidazole‐based anion transporters have been complexed to Au III to switch off their anion transport properties. In the presence of reducing agents such as GSH the gold is sequestered from the transporter and transport is switched on. This provides a method of targeting anion transporters to tissue with higher concentrations of GSH including tumors.